ASSESSMENT OF THE RELIABILITY OF INFORMATION IN THE COMPANY'S FINANCIAL STATEMENTS BASED ON MODELS J. MONTHIER, M. D. BENISHA AND M. L. ROXAS - Pedchenko, Nataliia; Milka, Alla; Artyukh-Pasyuta, Olena; Lozova, Oksana (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The article assesses the reliability of the information in the financial statements of PJSC "Morshinsky Mineral Water Plant "Oscar" for 2016-2020 based on the model of J. Montier (CScore), M. D. Benish (M-Score (8 variable), M L. Roxas (M-Score (5 variable). To assess the reliability of information in the financial statements of domestic economic entities of various forms and types of activity, it is proposed to use the model of M. D. Benish (8 variable) and M. L. Roxas (5 variable) based on the study of the essence, the order of application and justification of their advantages (relative ease of application, forecasting potential, breadth of use). The algorithm for calculating the indicators of the model of J. Montier (C-Score), M. D. Benish (M-Score (8 variable), M. L. Roxas (M-Score (5 variable) in accordance with the forms of financial reporting approved in Ukraine, which will allow determining the level of reliability of the reported information